Coffee Shop Businesses (Kepengen Coffee) To Survive the Economic Effects of a Pandemic by Restructuring Royalty Agreements - Winata, Ervin Kusuma (Universitas Wijaya Kusuma Surabaya, 2020)
Economic globalization in the last decade is developing very fast, the business world is always moving dynamically, business people are always looking for breakthroughs in growing their businesses one of which is a franchise system with the principles contained in the franchise agreement, but many companies are stalled due to co-19 virus pandemic so entrepreneurs must innovate and restructure to support the business. This is empirical legal research. The result of this paper is that principle of franchising is a pillar in a franchise agreement, and the parties in the franchise agreement have adhered to this agreement so that both parties need to fulfil these principles, due to the law that occurs due to a pandemic is a corporate restructuring and temporary agreement changes. The franchisor must think of regulations that benefit the franchisee with little risk. In restructuring the company and agreements, the franchisor must accurately measure the impact of the covid-19 pandemic on the franchisees' outlets.Keywords: franchising, principles, restructuring